“Removing the nail from the coffin'' outcomes of intramedullary nailing of femur fractures: a comparison of anterograde- and retrograde nails - Groenewald, Johann (Division of General Surgery, 2025)
Intramedullary (IM) nailing for femoral shaft fractures is the current most effective, gold-standard treatment modality for femoral shaft fractures in the adult population. In the past, intramedullary femur nails were primarily performed utilising the anterograde approach (AFN). Recently, the retrograde approach (RFN) has become an attractive alternative option. The retrograde approach requires no traction table during surgery, a viable solution where, in polytraumatized patients, multiple procedures might have to be combined. The retrograde insertion technique, conversely, utilizes a through-knee approach with potential injury to surrounding anatomical supporting structures of the knee. This approach also raises concerns about post-operative knee pain, stiffness and sepsis thus with a potential negative impact on functional knee scores. Methods: This is a retrospective review of a prospectively collected database of the HIV in Orthopaedic Skeletal Trauma (HOST) Study database. Patients who had an anterograde or retrograde femoral nail done in the HOST study were included in our data collection. Our primary aim was to compare the outcomes of AFN vs RFN comparing health-related quality of life measures. The secondary aim of our study was to compare the RFN and AFN groups with regards to surgical time and the incidence of complications, these including the presence of post-operative infections documented during subsequent follow-up visits. Results:196 patients underwent intramedullary nailing for diaphyseal femur fractures that was included in the study. 125 of them had an AFN performed and 71 a RFN. There was no significant difference in the compared health-related quality of life measures and its surrogate categories that represented post operative knee function. Both the AFN and RFN nailing techniques effectively accomplished high union rates and adequate alignment. Infection fortunately occurred at a very low rate within both the two groups. Conclusion: In the cohort of patients with femoral fractures treated with intramedullary nailing during the HOST study, anterograde - and retrograde femoral nails achieved similar outcomes with similar complication rates.